2015
DOI: 10.5897/ajfs2014.1241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal treatment on phenolic content, antioxidant, and -amylase inhibition activities of Moringa stenopetala leaves

Abstract: Moringa stenopetala is a socioeconomic valued tree that is widely available and cultivated in Southern part of Ethiopia. The leaves have been traditionally used as a food source with high nutritional and medicinal values. The present work was carried out to evaluate the effect of thermal treatment on the total phenolic content, total flavonoid content, antioxidant activities and α-amylase inhibition of aqueous leaf extracts obtained from M. stenopetala during maceration and different decoction time interval (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was previously reported that the IC50 value for the radical scavenging activity of M. stenopetala leaves powder was 59.5 g/mL after two weeks of extraction with 100% methanol [35]. For the aqueous decoction of M. stenopetala leaves powder, [36] found an IC50 value of 41.5 g/mL. M. olifiera had an IC50 of 62.94 g/mL when extracted with 70% ethanol, 122 g/mL when extracted with 50% methanol for three days, and 78.15 g/mL when extracted with aqueous decoction for five minutes [37].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the IC50 value for the radical scavenging activity of M. stenopetala leaves powder was 59.5 g/mL after two weeks of extraction with 100% methanol [35]. For the aqueous decoction of M. stenopetala leaves powder, [36] found an IC50 value of 41.5 g/mL. M. olifiera had an IC50 of 62.94 g/mL when extracted with 70% ethanol, 122 g/mL when extracted with 50% methanol for three days, and 78.15 g/mL when extracted with aqueous decoction for five minutes [37].…”
Section: Discussionmentioning
confidence: 99%